Pengaruh Penggunaan Media Sosial terhadap Tingkat Depresi dan Prokrastinasi Akademik pada Mahasiswa - Mega Pratiwi; Ramaulvi Muhammad Akhyar; Celine Aloyshima Haris (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Intensive social media use among university students has emerged as a global phenomenon closely correlated with declining psychological well-being and academic behavioral dysfunction. This study empirically examines the effect of social media use on depression levels and its subsequent impact on academic procrastination, positioning depression as a mediating variable. Adopting a quantitative explanatory design, the study sampled 58 undergraduate students from the Mathematics and Natural Sciences Education Department at Mulawarman University who were completing their final projects. Data were collected using three standardized instruments: the Social Media Use Integration Scale (SMUIS), Beck Depression Inventory-II (BDI-II), and Procrastination Assessment Scale for Students (PASS). Statistical analyses included validity, reliability, normality testing, multiple regression, and a mediation model based on the Baron & Kenny approach. Results indicated that social media use significantly predicted higher depression symptoms (b = 0.397, p < 0.001). Furthermore, depression fully mediated the relationship between social media use and academic procrastination (b = -0.103, p < 0.001), accounting for 78.9% of the variance in final-project delay behaviors. These findings confirm that digital platform engagement not only affects emotional well-being but also activates cognitive-affective mechanisms that drive academic task avoidance. Theoretical and practical implications are comprehensively discussed, including recommendations for cognitive-behavioral counseling interventions and digital literacy regulation within higher education settings.